Aplikasi Penyalut Berbahan Tepung Lidah Buaya untuk Mempertahankan Mutu Bunga Edibel - Emmy Darmawati; Adinda Putri Ayu Hakim (Institut Pertanian Bogor, 2023)
Edible flower is a flower that is safe for consumption both in fresh and processed form. In fresh form, edible flowers are used as garnishes or food decorations and a unique flavor enhancer. Kenikir (Cosmos sulphureus) is one of the edible flowers that are safe for consumption in fresh form. However, in fresh condition, flowers are easily damaged so that their market share is limited. Coating using aloe vera, which can hold moisture while having antimicrobial properties, is a method to maintain flower freshness. The purpose of the study was to examine the effect of aloe vera coating application to maintain the quality of kenikir as a fresh edible flower. The experimental design used was a two-factor completely randomized design with the first factor being the concentration of aloe vera flour (0.5% and 1%) and the second factor being spray frequency (1 application and 2 applications). Quality parameters measured during storage were respiration rate, weight loss, moisture content, and color. The results showed that the coating with the L2S2 formulation (1% aloe vera flour concentration with 2 applications) was the best treatment with a weight loss value of 7.3%, water content 82.57%, respiration rate 898.99 ml kg-1 hour-1, and has the highest brightness value. Based on these parameters, the L2S2 treatment could maintain the quality of kenikir as fresh edible flowers for up to 5 days compared to the control, which lasted 2 days at 10°C storage temperature. Keywords: aloe vera powder, coat spraying, Cosmos sulphureus, edible flower, kenikir flower